Physiological Changes and Trimester-Specific Reference Intervals for Complete Blood Count Parameters in Korean Pregnant Women - So, Heejin; Kwon, Kyungsuk; Jung, Sukhyun; Kim, Kyeongmi (Medicina (Kaunas, Lithuania), 2025)
Background and Objectives: Pregnancy induces numerous physiological changes, including hematologic adaptations, which affect complete blood count (CBC) parameters. Existing reference intervals for CBC are often based on non-pregnant populations, potentially limiting their clinical utility during pregnancy. This study aimed to evaluate longitudinal changes in CBC parameters throughout pregnancy in Korean women and to establish gestational age-specific reference intervals. Materials and Methods: This retrospective study, conducted between March and May 2025, included CBC tests consecutively performed on the same individuals at five time points: the first trimester (≤12 weeks), second trimester (13–28 weeks), third trimester (29–40 weeks), delivery day, and the second postpartum day. Additionally, to prevent duplication with the primary cohort, CBC data from pregnant outpatients and non-pregnant controls were also analyzed to establish reference intervals. CBC parameters were measured using an automated hematology analyzer. Reference intervals were established using the 2.5th and 97.5th percentile of the distribution. Results: During pregnancy, white blood cell (WBC) counts increased most significantly during the second trimester, while hemoglobin (Hgb) levels declined most markedly at this stage. Platelet (PLT) counts showed a consistent and progressive decline. The reference intervals for CBC parameters—WBC (×109/L), Hgb (g/dL), and PLT (×109/L)—were 5.11–12.14, 11.3–14.3, and 184–374 in the first trimester; 6.11–13.45, 10.1–13.3, and 164–356 in the second trimester; and 5.62–12.42, 10.1–14.1, and 145–349 in the third trimester, respectively. Conclusions: This study examined longitudinal changes in CBC parameters in Korean pregnant women and provided gestational age-specific reference intervals for CBC. This is expected to help clinicians interpret CBC results in pregnant women.